Hybrid Procedure in Aortoiliac Bifurcation and Femoral Lesion - Oktaviono, Yudi Her (Folia Medica Indonesiana, 2022)
Highlights: • A patient had a long segment of total occlusion to the proximal right common iliac and anterior tibial artery. • The treatment is a combination of percutaneous transluminal angioplasty (PTA) using vascular stent and the Fogarty thrombectomy. • Hybrid procedure can treat multilevel artery occlusive diseases, with shorter hospitalization, less perioperative morbidity, and similar early- and long-term efficacy. Abstract: Critical limb ischemia is a condition that threatens the viability of lower extremities and must be treated promptly to avoid major amputation. Revascularization is the most effective treatment method for critical limb ischemia. Revascularization using a hybrid of endovascular and open surgery is a minimally invasive procedure that performs well as the treatment for medically high-risk patients. A hybrid procedure should be considered for patients with high surgical risk. However, there are factors that could compromise its long-term patency, such as critical limb ischemia and diabetes. This study reported a case of a 53-year-old Asian male with history of insulin-dependent diabetes mellitus and long-standing tobacco use, presented with pain in the right leg at rest approximately 30 days prior to admission. Physical examination revealed a low temperature and remarkable non-palpable pulses in the right femoral, posterior tibial, and dorsalis pedis segments. Arteriography with run-offs revealed a long segment of total occlusion from the proximal right common iliac and anterior tibial artery. There was non-significant stenosis in the right popliteal artery. The patient was treated using a combination of percutaneous transluminal angioplasty (PTA) of the right common iliac artery using vascular stent and the Fogarty thrombectomy of the common femoral artery, equipped with an X-ray system and a moveable radiolucent surgical table. The anticoagulant used on the patient during the procedure was heparin. There was no residual stenosis after the procedure on the occlusion along the right common iliac artery to the common femoral artery. In conclusion, multilevel artery occlusive diseases could be treated by hybrid procedure, with shorter hospitalization, less perioperative morbidity, and similar early- and long-term efficacy compared with open revascularization.